Automotive cybersecurity: assessing a new platform for cybercrime and malicious hacking. - Kennedy, Jay; Holt, Thomas; Cheng, Betty (Journal of Crime & Justice, 2019)
The push for technological enhancement and Internet connectivity in all aspects of modern life is radically transforming our use of devices and equipment that was not designed with this functionality. In fact, technological enhancements are transforming the automotive industry by increasing the number of components within the vehicle that are controlled by computers and which provide information to remote systems by various communications methods. These changes create new opportunities for cybercrime, particularly acts of cyber-trespass by computer hackers. This study considers how these technical threats may be limited through the use of criminological theory, specifically a routine activities perspective. The role of various actors in the automotive supply chain, and their potential function to deter and mitigate threats are discussed. The implications of this study for theory and practice are discussed in depth.